The Geographical Legacies of Mountains: Impacts on Cultural Difference Landscapes. Issue 1 (2nd January 2018) - Wu, Wenjie; Wang, Jianghao; Dai, Tianshi; Wang, Xin (Mark)
Abstract : Large-scale mountains that affect civilized linguistic exchanges over space offer potentially profound cultural difference landscape implications. This article uses China's national trunk mountain system as a natural experiment to explore the connection between spatial adjacency of mountains and cultural difference landscapes. Our spatial design documents that the presence of mountains widens the linguistic difference between two cities located on the opposite mountain sides, particularly when they are adjacent to administrative borders. The effect dwindles as spatial contiguity margins between city pairs increases. The results shed light on the importance of conceptualizing geographic contextual constraints to the configuration of cultural difference landscapes.